Leverage Keuangan Dan Likuiditas Saham Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Jakarta - I Made Sudana; Nurul Intan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
This research focus on the effect of financial leverage on stock liquidity, with control variables included stock risk, return on assets, market capitalization, volume, institutional ownership during 2003-2004. This research used 86 manufacture company that listing in Jakarta Stock Exchange. Analysis method use multivariate regression. The result of partial multivariate regression indicates that financial leverage as independent variable and control variables include stock risk, return on assets, market capitalization, volume, institutional ownership have positive impact on stock liquidity. Independent variable is financial leverage and control variables include return on assets, volume, institutional ownership have significant impact on stock liquidity, while other control variables such as stock risk and market capitalization have not significant impact on stock liquidity. Simultaneously, financial leverage, stock risk, return on assets, market capitalization, volume, institutional ownership have significant impact on stock liquidity.